2020
DOI: 10.1371/journal.pone.0241572
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of asymptomatic neurosyphilis among HIV-negative serofast patients in China: A meta-analysis

Abstract: Introduction Neurosyphilis can occur at any stage of syphilis. After treatment, 30%-40% of syphilis patients remained serofast. But the prevalence of asymptomatic neurosyphilis (ANS) among serofast syphilis patients remains unclear. Untimely treatment or improper management for ANS may result in neurological complications. So we perform the meta-analysis to evaluate the prevalence of ANS cases among HIV-negative serofast syphilis patients for exploring their relationship and addressing their clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Male, MSM, advanced age (≥45 years), PLWH without combined antiretroviral therapy, drug use disorder, lack of antisyphilitic therapy, reinfection after a previous syphilis infection, and patients in serofast state are risk factors for neurosyphilis, especially the late forms (8)(9)(10)(11). Elevated serum and cerebrospinal fluid (CSF) rapid plasma reagin (RPR) titer, CSF protein concentration, and increased burden of the cerebral small vessel diseases may indicate the aggravation of neurological symptoms (10,12,13). Specific subtypes of T. pallidum are more likely to induce neurosyphilis; for instance, subtype 14d is the most common neurosyphilisrelated genotype in China (14).…”
Section: Epidemiologymentioning
confidence: 99%
“…Male, MSM, advanced age (≥45 years), PLWH without combined antiretroviral therapy, drug use disorder, lack of antisyphilitic therapy, reinfection after a previous syphilis infection, and patients in serofast state are risk factors for neurosyphilis, especially the late forms (8)(9)(10)(11). Elevated serum and cerebrospinal fluid (CSF) rapid plasma reagin (RPR) titer, CSF protein concentration, and increased burden of the cerebral small vessel diseases may indicate the aggravation of neurological symptoms (10,12,13). Specific subtypes of T. pallidum are more likely to induce neurosyphilis; for instance, subtype 14d is the most common neurosyphilisrelated genotype in China (14).…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies have shown that T. pallidum can disseminate to the central nervous system of rabbits within hours to days after inoculation ( 1 ). In recent years, with the increasing prevalence of syphilis around the world, the incidence of neurosyphilis has also increased markedly each year ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, 36 cases of syphilis per 100,000 people were reported in China. 1,2 Syphilis, also called the "great imitator", can have various symptoms, making diagnosis difficult. 3,4 Syphilis is treated with antibiotics; 5 however, if it is not treated on time and the Treponema pallidum invades the nervous system, it leads to neurosyphilis.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Syphilis is treated with antibiotics; 5 however, if it is not treated on time and the Treponema pallidum invades the nervous system, it leads to neurosyphilis. 1,2 Neurosyphilis usually occurs about 10 to 20 years after being first infected with syphilis. 5 It can be classified according to whether symptoms are present as symptomatic or asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation